(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article describes the use of various interactive methods, in particular, the use of the "Project Work" method, in primary-grade mother tongue classes. In addition, there are opinions about the effectiveness of using interactive methods in the educational process.